Innovative architecture of on-board and on-ground radio systems for space communication - Cinarelli, Davide <1983> (Alma Mater Studiorum - Università di Bologna, 2012)
The radio communication system is one of the most critical system of the overall satellite platform: it often represents the only way of communication, between a spacecraft and the Ground Segment or among a constellation of satellites. This thesis focuses on specific innovative architectures for on-board and on-ground radio systems. In particular, this work is an integral part of a space program started in 2004 at the University of Bologna, Forlì campus, which led to the completion of the microsatellite ALMASat-1, successfully launched on-board the VEGA maiden flight. The success of this program led to the development of a second microsatellite, named ALMASat-EO, a three-axis stabilized microsatellite able to capture images of the Earth surface. Therefore, the first objective of this study was focused on the investigation of an innovative, efficient and low cost architecture for on-board radio communication systems. The TT&C system and the high data rate transmitter for images downlink design and realization are thoroughly described in this work, together with the development of the embedded hardware and the adopted antenna systems. Moreover, considering the increasing interest in the development of constellations of microsatellite, in particular those flying in close formations, a careful analysis has been carried out for the development of innovative communication protocols for inter-satellite links. Furthermore, in order to investigate the system aspects of space communications, a study has been carried out at ESOC having as objective the design, implementation and test of two experimental devices for the enhancement of the ESA GS. Thus, a significant portion of this thesis is dedicated to the description of the results of a method for improving the phase stability of GS radio frequency equipments by means of real-time phase compensation and a new way to perform two antennas arraying tracking using already existing ESA tracking stations facilities.